International migration policies : government views and priorities (Statistical Papers - United Nations (Ser. A), Population and Vital Statistics Report,, 2013)
This report provides an overview of Government views and policies on international migration for 196 countries, including all 193 Member States, and three non-member States of the United Nations. The report describes Government views and policy intentions related to immigration and emigration, and how these have evolved over time with changing international migration patterns.